Media Construction in Regional Conflict:Framing Analysis of The Island Dispute Between Aceh and North Sumatera in Tempo.Com and Kumparan.Com Reporting - Ari Oldwin Sitorus; Hasan Sazali; Retno Sayekti (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze how the mass media constructs the discourse of territorial conflict through reporting on the dispute over four islands in the waters of Aceh Singkil that were transferred to North Sumatra. This study highlights how two national media, Tempo.com and Kumparan.com, frame the issue of territorial boundaries that are administratively, politically, and economically sensitive. The novelty of this study lies in the comparative framing approach between the two media with different journalism styles, as well as their relationship to the potential for socio-political escalation at the local level. This study uses a qualitative method with Robert Entman's framing analysis model approach, which examines four main elements: define problems, diagnose causes, make moral judgments, and suggest remedies. The results show that Tempo.com tends to frame the conflict as an administrative and technocratic problem that is resolved through legal channels and cross-institutional coordination, while Kumparan.com emphasizes the economic dimension by highlighting the potential for oil and gas reserves on the disputed islands, opening up space for public speculation, and encouraging collaborative solutions between regions. This difference in framing emphasizes the role of the media in shaping public perception and maintaining the stability of the narrative on the issue of territorial conflict in Indonesia.